A review on introduction and applications of starch and its biodegradable polymers - Pokhrel, Shanta (International Journal of Environment, 2015)
Biodegradable polymers play a very important role in plastic engineering by replacing non biodegradable, non renewable petrol based polymers. Starch is a renewable, biodegradable, low cost natural polymer with high availability. Natural polymers can be blended with synthetic polymers to improve their properties significantly. This article reviews advance in starch and starch based blends and presents their numerous potential applications. Therefore, this review helps to understand the importance and characteristics of starch and its biodegradable polymers (blends) by its various aspects such as structural properties and wide applications.International Journal of Environment Vol.4(4) 2015: 114-125